Microstructure and Hydrogen Permeability of Nb-Ni-Ti-Zr-Co High Entropy Alloys; Membranes; Vol. 12, iss. 11 - Krotkevich D. G. Dmitry Georgievich; Kashkarov E. B. Egor Borisovich; Koptsev M. Maksim; Svyatkin L. A. Leonid Aleksandrovich; Travitsky (Travitzky) N. Nakhum; Lider A. M. Andrey Markovich (2022, 2022)
Title screen